2019
DOI: 10.1177/1082013219858529
|View full text |Cite
|
Sign up to set email alerts
|

Extract of Mangifera indica L. leaves may reduce biofilms of Staphylococcus spp. in stainless steel and teatcup rubbers

Abstract: Human ingestion of antimicrobial residues in dairy products is a problem of public health. In this study we evaluated antibacterial effectiveness of aqueous and ethanolic leaf extracts of Mangifera indica L. as a natural alternative for reduction of Staphylococcus spp. biofilms. Eight Staphylococcus spp. strains from cows with mastitis and the Staphylococcus aureus strain (ATCC 25923) were evaluated. High performance liquid chromatography indicated the presence of phenolic compounds in the aqueous extract. Agi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
11
0
5

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 39 publications
2
11
0
5
Order By: Relevance
“…This investigation has also revealed their potentiality in controlling the microbial growth. [31]. In the present study with a lesser amount of extract namely 30 microlitres, good inhibition was seen.…”
Section: Discussionsupporting
confidence: 57%
“…This investigation has also revealed their potentiality in controlling the microbial growth. [31]. In the present study with a lesser amount of extract namely 30 microlitres, good inhibition was seen.…”
Section: Discussionsupporting
confidence: 57%
“…This biofilm can prolong the time of colonization and infection, as well as the dispersion to different parts of the human body. 4,5,7 Infections develop from the deepening of this bacterium by a solution of tissue continuity due to trauma, skin or surgical lesions. These infections generate purulent material forming abscesses and can cause minor infections of the skin and soft tissues and invasive infections such as: infections of the central nervous system, respiratory, gastrointestinal and urinary tract, bacteraemia and osteomyelitis.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, traditional medicine and phytotherapy has been gaining increasing strength since a wide variety of plants show that they have biological properties for the different conditions that man presents, so there is a great empirical source of active ingredients, it is convenient to clarify those properties. [1][2][3][4] Currently, bacterial resistance against antibiotics has been increasing, resulting in a worldwide concern since mild infections cannot be controlled. This caused by the inappropriate and excessive use of drugs in addition to deficiencies in the prevention and control of infections.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, a methanol extract of the seed kernal of MI has been found to exert inhibitory effects against Staphylococcus aureus, Escherichia coli and Bacillus subtilis (29). In the study by Manzur et al (30), aqueous and ethanolic extracts of MI leaves were found to exert inhibitory effects against Stapylococcus species isolated from cows. In another study, Mushore and Matuvhunye (31) demonstrated that an aqueous extract of stem bark of MI can reduce the growth of S. aureus.…”
Section: Antioxidant Propertiesmentioning
confidence: 99%